Augmentation of Dermal Wound Healing by Adipose Tissue-Derived Stromal Cells (ASC) - Van Dongen, Joris A.; Harmsen, Martin C.; Van der Lei, Berend; Stevens, Hieronymus P. (Bioengineering (Basel), 2018)
The skin is the largest organ of the human body and is the first line of defense against physical and biological damage. Thus, the skin is equipped to self-repair and regenerates after trauma. Skin regeneration after damage comprises a tightly spatial-temporally regulated process of wound healing that involves virtually all cell types in the skin. Wound healing features five partially overlapping stages: homeostasis, inflammation, proliferation, re-epithelization, and finally resolution or fibrosis. Dysreguled wound healing may resolve in dermal scarring. Adipose tissue is long known for its suppressive influence on dermal scarring. Cultured adipose tissue-derived stromal cells (ASCs) secrete a plethora of regenerative growth factors and immune mediators that influence processes during wound healing e.g., angiogenesis, modulation of inflammation and extracellular matrix remodeling. In clinical practice, ASCs are usually administered as part of fractionated adipose tissue i.e., as part of enzymatically isolated SVF (cellular SVF), mechanically isolated SVF (tissue SVF), or as lipograft. Enzymatic isolation of SVF obtained adipose tissue results in suspension of adipocyte-free cells (cSVF) that lack intact intercellular adhesions or connections to extracellular matrix (ECM). Mechanical isolation of SVF from adipose tissue destructs the parenchyma (adipocytes), which results in a tissue SVF (tSVF) with intact connections between cells, as well as matrix. To date, due to a lack of well-designed prospective randomized clinical trials, neither cSVF, tSVF, whole adipose tissue, or cultured ASCs can be indicated as the preferred preparation procedure prior to therapeutic administration. In this review, we present and discuss current literature regarding the different administration options to apply ASCs (i.e., cultured ASCs, cSVF, tSVF, and lipografting) to augment dermal wound healing, as well as the available indications for clinical efficacy.